2001
DOI: 10.1002/ajpa.1118
|View full text |Cite
|
Sign up to set email alerts
|

Founding Amerindian mitochondrial DNA lineages in ancient Maya from Xcaret, Quintana Roo

Abstract: Ancient DNA from the bone remains of 25 out of 28 pre-Columbian individuals from the Late Classic-Postclassic Maya site of Xcaret, Quintana Roo, was recovered, and mitochondrial DNA (mtDNA) was amplified by using the polymerase chain reaction. The presence of the four founding Amerindian mtDNA lineages was investigated by restriction analysis and by direct sequencing in selected individuals. The mtDNA lineages A, B, and C were found in this population. Eighty-four percent of the individuals were lineage A, whe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
32
0
3

Year Published

2003
2003
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(43 citation statements)
references
References 13 publications
8
32
0
3
Order By: Relevance
“…The Mexican Maya in this study displayed the highest frequency of haplogroup A, similar to the ancient Postclassic Aztecs from Tlatelolco (1450-1275 CE), Mexico (Kemp et al 2005), the Maya from Xcaret, Mexico (González-Oliver et al 2001), and the most modern Maya. In contrast, a 650-1200 CE Maya sample from Copán, Honduras, exhibited a high frequency of haplogroup C (Merriwether et al 1997), and the 800-1100 CE from the Tommy site in the United States (Snow et al 2010) showed a high frequency of haplogroup B, most closely resembling the ancient Anasazi at Fremont (Carlyle et al 2000;LeBlanc et al 2007) and the modern populations of Cora, Hualapai, Huichol, Jemez, Tarahumara, Tohono O'odham, and Zuni , the Tojolabal Maya (González-Martín et al 2015), and US Southwest and South America (Salas et al 2009;Raff et al 2011).…”
Section: Haplotype Analysis and Shared Haplotypessupporting
confidence: 73%
“…The Mexican Maya in this study displayed the highest frequency of haplogroup A, similar to the ancient Postclassic Aztecs from Tlatelolco (1450-1275 CE), Mexico (Kemp et al 2005), the Maya from Xcaret, Mexico (González-Oliver et al 2001), and the most modern Maya. In contrast, a 650-1200 CE Maya sample from Copán, Honduras, exhibited a high frequency of haplogroup C (Merriwether et al 1997), and the 800-1100 CE from the Tommy site in the United States (Snow et al 2010) showed a high frequency of haplogroup B, most closely resembling the ancient Anasazi at Fremont (Carlyle et al 2000;LeBlanc et al 2007) and the modern populations of Cora, Hualapai, Huichol, Jemez, Tarahumara, Tohono O'odham, and Zuni , the Tojolabal Maya (González-Martín et al 2015), and US Southwest and South America (Salas et al 2009;Raff et al 2011).…”
Section: Haplotype Analysis and Shared Haplotypessupporting
confidence: 73%
“…These studies have shown a substantial contribution of Native American ancestry to extant Mexican Mestizo populations, supported by additional studies based on mtDNA sequences (González-Oliver et al 2001;Green et al 2000;Kemp et al 2010;Peñaloza-Espinosa et al 2007;Sandoval et al 2009;Torroni et al 1994). Other studies have also described the paternal genetic diversity in Mexican 4 indigenous groups (Barrot et al 2005;Felix-Lopez et al 2006;Kemp et al 2010;PaezRiberos et al 2006;Rangel-Villalobos et al 2000); however, a better understanding could be gained by putting this characterization into context with the continental landscape.…”
Section: Introductionmentioning
confidence: 78%
“…Earlier reports have shown that the frequency of haplogroup C1 varies across distinct native American ethnic groups in Mexico, having a frequency similar to haplogroup B2. 16,29 C1 haplogroup is defined by polymorphisms C16223T, T16298C, T16325C, C16327T, A73G, A263G, and the adenine deletions at positions 249, 290 and 291 of HVR2. [26][27][28] The haplotype Mx144 had the characteristic polymorphisms of C1 haplogroup and it was the most commonly detected (five individuals; Table 1).…”
Section: Mitochondrial Haplogroupsmentioning
confidence: 99%
“…15,24,25 Those Amerindian haplogroups were recently termed A2, C1, B2 and D1, once there were more available data of the complete mtDNA genome sequence. [26][27][28] As most studies that analyzed mtDNA polymorphism in the Mexican population used mainly restriction fragment length polymorphisms (RFLPs), 13,17,18,29 and there are no available data from full control region sequences, the knowledge of mtDNA diversity is limited and it has not been extensively analyzed.…”
Section: Introductionmentioning
confidence: 99%